A multicenter real‐world review of 10 kHz SCS outcomes for treatment of chronic trunk and/or limb pain. Issue 3 (22nd January 2019) - Stauss, Thomas; El Majdoub, Faycal; Sayed, Dawood; Surges, Gernot; Rosenberg, William S.; Kapural, Leonardo; Bundschu, Richard; Lalkhen, Abdul; Patel, Nileshkumar; Gliner, Bradford; Subbaroyan, Jeyakumar; Rotte, Anand; et al.
Abstract: Objectives: High‐frequency spinal cord stimulation (HF‐SCS) at 10 kHz has proven to be efficacious in the treatment of chronic back and leg pain in a randomized, controlled, trial (SENZA‐RCT). However, large observational studies have yet to be published. Therefore, we performed a real‐world, multicenter, retrospective, review of therapy efficacy in 1660 patients with chronic trunk and/or limb pain. Methods: Data were collected in a real‐world environment and retrospectively sourced from a global database. Included patients were trialed and/or permanently implanted with HF‐SCS at 10 kHz between April 2014 and January 2018. We evaluated responder rates at 3, 6, and 12 months post‐implantation. Response was defined as ≥50% pain relief from baseline. A last visit analysis included responder rate along with overall change in function, sleep, quality of life, and medication intake versus baseline. Results: Eighty‐four percent of our HF‐SCS‐treated patients had both chronic back and leg pain. At least 70% of patients reported response to therapy throughout 12 months of follow‐up. This sustained responder rate was corroborated by the last visit value (74.1%). Most patients reported concomitant improvements in function (72.3%), sleep (68.0%), and quality of life (90.3%) at their last visit versus baseline. Thirty‐two percent of patients reported decreased medication intake at their last visit. Interpretation: Sustained and effective pain relief was experienced by >70% of our HF‐SCS‐treated patients, consistent with the findings of a previously published randomized, controlled, trial. Our review provides complementary evidence to support the treatment of chronic back and leg pain with this therapy.